Laboratory facilities for engineering technology programs in Malaysian technical universities - Mohd Ismail, Kamsiah; Radin Salim, Kamilah; Haron, Habibah Norehan; Abd Rahman, Rozita Juliana; Hussain, Noor Hamizah; Ali, Rosmah; Abdullah, Morina; Mohamed Nor, Norhayati; Mohamed, Zainai; Mulop, Normah (University Teknologi Malaysia, 2016)
Malaysia has put emphasis on Engineering Technology programs in its effort to be a developed country by 2020. This demand for Engineering Technology programs to be implemented is to increase the number of technical graduates for the industry needs. The Malaysian Technical University (MTUN) institutions and UniKL are among the higher education institutions in Malaysia that offer Engineering Technology programs at the undergraduate level. These institutions main agenda is to produce skilled work-ready graduates. Being in its infancy, MTUN has yet to produce their first batch of Engineering Technology graduates. This article reports the evaluation of the facilities at MTUN, as part of a bigger research scope. The data collection method in this study is mainly qualitative, which comprise of interviews, observations and document analysis. The interview protocol and observation checklist were developed and validated by experts and found reliable after running a set of pilot interview and observation. Interviews were carried out on the lecturers, whereas observations were made in the classroom, laboratories and a teaching factory. Document analysis that was carried out was on the Code of Practice for Program Accreditation (COPPA) document. This study also adopted the quantitative method using survey questions on students’ satisfaction of the facilities related to the application-based practice oriented at the institutions. From the laboratories observations, interviews with the lecturers, analysis of COPPA document and survey questionnaires answered by students, it can be concluded that the laboratory facilities provided by the three MTUN are adequate for the current number of students.